IgA antibody-producing cells in peripheral blood after antigen ingestion: evidence for a common mucosal immune system in humans. - Czerkinsky, C (1987)
The finding that ingestion of antigens results in the selection induction of IgA antibodies in external secretions suggests that antigen sensitizes Peyer's patch lymphoid cells, which migrate to mucosal sites and generate local secretory IgA (S-IgA) antibody responses. Evidence for a common mucosal immune system in humans has been scanty because of the difficulty in demonstrating migratory behavior of Peyer's patch cells. In the present study, peripheral blood mononuclear cells (PBMC) from human volunteers who had ingested capsules containing killed Streptococcus mutans were assayed for spontaneous antibody-producing cells. Four of five volunteers exhibited circulating IgA-producing cells within 7 days and reached maximum responses by days 10-12. One IgA-deficient subject exhibited IgM responses with identical kinetics. Pokeweed-mitogen-stimulated PBMC produced anti-S. mutans antibodies predominantly of the IgA isotype. Significant S-IgA anti-S. mutans antibodies were detected in saliva and tears by day 14, and the antibodies reached maximum titers by 3 weeks. No changes in serum anti-S. mutans antibodies were noted. The IgA-deficient subject produced salivary secretory IgM antibodies. These results suggest that, after antigen ingestion, peripheral blood contains antigen-specific precursors of IgA plasma cells and that their presence precedes the appearance of S-IgA antibodies in external secretions. Therefore, these experiments provide further support for the existence of a common mucosal immune system in humans.